Last man standing : media, framing, and the 2012 Republican primaries - Coombs, Danielle Sarver (Communication, media, and politics., 2014)
"When Barack Obama was re-elected president in November 2012, his Republican challenger, Mitt Romney, took the blame for being alternately too moderate or too conservative; his vast wealth made him unappealing to voters; and his robotic persona meant he just could not connect. How, then, did he win the nomination? This book examines mainstream media coverage of the 2012 Republican primary season to identify and examine the frames used to make sense of the candidates and the race."--